Games as Windows and Remedies to Modern Society: A Qualified Defense of Agonistic Encounters - Francisco Javier López Frías (Praxis Filosófica)
In this article, I explore connections among sport, competition, and capitalist society by drawing from works in the philosophy of sport and critical theory. Initially, I identify games, especially sports, as fundamental activities in contemporary life. In particular, I claim that the glorification of victory in sporting contests permeates the attitude toward competition of individuals in capitalist societies. Thus, sports can be understood as windows to observe the “achievement ethos” inherent in capitalism. Subsequently, I explore both philosophical victory-centric and mutualistic views of sporting competition. What follows from this examination is that competition itself is not inherently negative. It becomes detrimental when pursued at any cost. In alignment with Robert L. Simon’s sport mutualism, I advocate that competition may yield positive moral and social outcomes when approached as a “mutual quest for excellence.” To conclude, I trace this positive, mutualistic conception of competition back to ancient Greek and post-Hellenic reflections on agōn and excellence.